Design And Analysis Of Substrate Integrated Waveguide Antenna Performance For Material Characterization (Teflon) - Kamleshvari, Panerselvan (2022)
The demand of small size electronic systems has been increasing from several years. Patch antennas are one of the most attractive antennas for integrated RF front-end systems due to their compatibility with microwave integrated circuits. The rectangular patch antenna is easy to construct and analysis. Substrate Integrated Waveguide (SIW) was studied as a class of efficient integrated transmission lines compatible with planar technologies, offering incomparable self-consistent shielding and high-quality factor performances. In this paper, the proposed microstrip rectangular patch antenna is simulated at 2.4 GHz resonance frequency analysis performance of substrate integrated waveguide antenna with material characterization by using Teflon (polytetrafluorethylene) as its substrate and different height of the substrates were investigated. For the simulation, antennas are numerically investigated using High Frequency Structure Simulator (HFSS) software. This is how the maximum extraction can be done from a simple microstrip patch antenna by using a Teflon substrate. The simulation results were taken and are shown in the paper. The simple structured configuration and low profile of the proposed antenna makes the fabrication process easy